The web of D-branes at singularities in compact Calabi-Yau manifolds - Cicoli, Michele; Sauerland, Sven; Mayrhofer, Christoph; Quevedo, Fernando; Valandro, Roberto (Journal of high energy physics, 2013)
We present novel continuous supersymmetric transitions which take place among different chiral configurations of D3/D7 branes at singularities in the context of type IIB Calabi-Yau compactifications. We find that distinct local models which admit a consistent global embedding can actually be connected to each other along flat directions by means of transitions of bulk-to-flavour branes. This has interesting interpretations in terms of brane recombination/splitting and brane/anti-brane creation/annihilation. These transitions give rise to a large web of quiver gauge theories parametrised by splitting/recombination modes of bulk branes which are not present in the non-compact case. We illustrate our results in concrete global embeddings of chiral models at a dP0 singularity.